Learning by Playing. A Case Study of the Education in Photography by Digital Games - Mago, Zdenko; Wojciechowski, Łukasz P.; Balážiková, Magdaléna; Shelton, Amiee J. (Journal of Education Culture and Society, 2023)
Aim. The study aims to explore the current state of digital game-based learning to reflect the extent, possibilities, opportunities, and limitations of its implementation in the specific field of education as visual art, especially photography. Method. The explorative study employed the method of theoretical analysis of available literature and other secondary sources related to the issue, and subsequently applied the method of an illustrative (descriptive) case study. Results. Photo modes of commercially available digital games, originally intended to increase the players’ retention and participation, have led to the birth of a new art form, virtual photography. The technology of photo modes in a larger variety of recent games has made virtual photography available to significantly more players. Photo modes provide artistic control and creative options alongside a whole catalogue of lenses, camera parameters, and other features, reducing the financial burden associated with the purchase of photographic equipment. Furthermore, photo modes offer more than just a substitutable alternative to traditional photography, as added artistic value is found within virtual worlds. Conclusions. Despite some limitations regarding the overall implementation of digital game-based learning in photography classrooms, photo modes of commercially available digital games are a suitable tool for educational efforts in photography through both self-development and measurement of outcome-based learning.